Sustainable hybrid coating on Ti-alloy—synthesize and characterization - Maleque, Md. Abdul; Abdul Aziz, Adam Nuqman; Hj Hassan, Masjuki; Efeoglu, Ihsan (Springer, 2025)
The environmental susceptibility of Ti-alloy adversely affects its mechanical properties, operational capability, and friction encountered through surface interaction has been recognized, resulting in wear, corrosion, and fatigue of the material. Therefore, this study focused on the synthesis and characterization of hybrid environmentally friendly silicon carbide-graphene oxide coating on Ti-alloy using liquid additive manufacturing (LAM) approach. The work encompassed the investigation of surface topography, microstructure, phase constituents, and microhardness of the LAM-processed hybrid coated Ti-alloy, employing optical microscopy, scanning electron microscopy, X-ray diffraction, and microhardness testing. Following the Taguchi design of experiments, nine samples were prepared with variations in factors such as current (70, 80 and 90 A), voltage (15, 20 and 35 V), silicon carbidegraphene oxide (70–30, 75–25 and 80–20 wt%) at a constant speed of 1.5 mm/ s. The micrograph study revealed a dendritic microstructure as the predominant morphology of the hybrid coated material. Phase analysis showed the presence of intermetallic compounds on the coated surface. The hardness of hybrid coated Tialloy was increased by 3–4 times compared to the substrate material. The optimal parameter settings for both morphology and hardness, are a silicon carbide-graphene oxide composition of 80–20 wt%, a current of 90 A, and a voltage of 20 V.